2017
DOI: 10.1103/physrevlett.118.048003
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Rearrangements and their Rheological Implications in a Model Thixotropic Elastoviscoplastic Fluid

Abstract: We identify the sequence of microstructural changes that characterize the evolution of an attractive particulate gel under flow and discuss their implications on macroscopic rheology. Dissipative particle dynamics is used to monitor shear-driven evolution of a fabric tensor constructed from the ensemble spatial configuration of individual attractive constituents within the gel. By decomposing this tensor into isotropic and nonisotropic components we show that the average coordination number correlates directly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 52 publications
3
56
0
Order By: Relevance
“…Also similarly to previous works 31,34,35 , we find that the maximum anisotropy is reached at the yielding point. After this point, the initial gel structure is lost due to the bonds breakage, thereby decreasing the amount of stored stress and consequent anisotropy.…”
Section: Discussionsupporting
confidence: 91%
“…Also similarly to previous works 31,34,35 , we find that the maximum anisotropy is reached at the yielding point. After this point, the initial gel structure is lost due to the bonds breakage, thereby decreasing the amount of stored stress and consequent anisotropy.…”
Section: Discussionsupporting
confidence: 91%
“…Stress overshoots in shear start up experiments are commonly observed in both dense hard sphere systems [40], but also in network forming colloidal gels [42]. In the latter case, the stress overshoot is closely related with the change of structural quantities, while in the former case, which is of our interests, the stress overshoot depends on the relaxation level (age) of the system [14,40,41].…”
Section: Static Yield Stress and The Stress Overshootmentioning
confidence: 94%
“…Since flow strength can be characterized by the shear rate, or in dimensionless form by the Mason number, and the accumulated strain provides a convenient dimensionless measure of the time over which transport processes take place, we refer to this framework as a interacting particles. In this scheme, colloidal particles interact through Morse potential, as well as random, dissipative and lubrication forces, excluding traditional conservative forces in order to avoid discontinuities in particle interaction potentials (For details of simulation method refer to Supplementary Material and [12,18]). Having the exact expression for the interaction potentials, one can accordingly calculate the effective range of attraction using the Noro-Frankel expression [43]; however, it has been shown that the stickiness parameter and the second virial component of all interaction potentials become virtually identical at short distances where the separation between two particles is smaller than 0.1-0.3a [43,44].…”
Section:  mentioning
confidence: 99%
“…The residual stress ( r  ), but they also have distinctly different micro-and meso-scale structures than the gels formed under quiescent conditions. Analysis of the fractal dimension of the gels using a 13 | P a g e box counting algorithm [12] shows that at intermediate shearing times, 10 Using these criteria elucidated above, we can construct a phase map of the different regimes and the corresponding microstructures ( Fig.4) using our direct numerical simulations of each regime.…”
Section:  mentioning
confidence: 99%
See 1 more Smart Citation